Age Differences in Heritability of a Latent Dementia Index Score in Men and Women. (20th December 2022) - Luczak, Susan E; Beam, Christopher R.; Tureson, Kayla; Reynolds, Chandra A.; Panizzon, Matthew S.; Lee, Teresa; Sachdev, Perminder S.; Gatz, Margaret; ,
Abstract: Background: Heritability estimates of dementia are ∼50‐60% of the total variance across older adulthood. Earlier age of onset, however, might be associated with greater genetic influence whereas older age of onset might be associated with greater environmental influences. The categorical nature of dementia diagnosis outcomes has made testing the relative importance of genetic and environmental influences on dementia difficult due to low statistical power. To overcome this methodological limitation, we tested linear and quadratic effects of age on genetic and environmental variance underlying a continuous measure of dementia likelihood in men and women. Method: The analytic sample was 5, 670 (53% female) pairs of twins from 10 studies in the Interplay of Genes and Environment Across Multiple Studies (IGEMS) consortium. Dementia likelihood is quantified continuously using a latent dementia index measure that is estimated from twins' available cognitive, memory‐specific, and functional ability measures. Linear and quadratic age differences in genetic and environmental influences on dementia likelihood were tested by modeling univariate correlation between twins' dementia scores as a linear function of zygosity and age in M plus . Separate models were estimated for male and female twin groups. Results: Age moderated genetic and environmental influences on dementia likelihood scores. Both genetic and nonshared environmental variance increased as a function of age, whereas common environmental variance declined. Sex significantly moderated the effect of zygosity on the twin correlations (monozygotic male: .57, monozygotic female: .51, dizygotic male: .19, dizygotic female: .25). Notably, MZ twin correlations were consistent with previously reported heritability estimates for dementia. The pattern of age moderation was the same in men as women, although the linear effect of age on both genetic and common environmental influences was greater in men than women (see Figure 1). Conclusion: Age linearly moderated genetic and environmental variance underlying dementia likelihood similarly for both men and women, despite quantitative genetic and environmental sex differences in dementia likelihood. Genetic variance accounted for similar proportions of total variance at younger ages, whereas genetic variance accounted for greater variance in men than in women at older ages.